2014
DOI: 10.1111/ajd.12126
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein stimulates collagen synthesis by activating the TGF‐β/smad signal pathway

Abstract: The results showed that daidzein treatment can increase skin collagen synthesis and inhibit collagen degradation in vitro and in vivo. It seems that TGF-β/smad signalling pathways play an important role in daidzein-induced collagen accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
(36 reference statements)
3
26
0
Order By: Relevance
“…Therefore, we characterized the levels of TGF‐β to define its role in the enhancement of wound healing following BV treatment. Additionally, multiple studies have demonstrated the TGF‐β‐dependent induction of collagen expression and synthesis in dermal fibroblasts (Dang et al, ; Wu et al, ; Zhao et al, ). BV treatment of diabetic wounds resulted in the up‐regulation of TGF‐β and enhanced CD31 expression compared to vehicle‐treated diabetic wounds, and these effects were observed from the earliest stages of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we characterized the levels of TGF‐β to define its role in the enhancement of wound healing following BV treatment. Additionally, multiple studies have demonstrated the TGF‐β‐dependent induction of collagen expression and synthesis in dermal fibroblasts (Dang et al, ; Wu et al, ; Zhao et al, ). BV treatment of diabetic wounds resulted in the up‐regulation of TGF‐β and enhanced CD31 expression compared to vehicle‐treated diabetic wounds, and these effects were observed from the earliest stages of the study.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is the major activator of collagen synthesis in human skin fibroblasts. The TGF-β type 1 receptor initiates the synthesis of type 1 procollagen [39]. UV irradiation impairs TGF-β and Smad2/3…”
Section: Regulatory Effect Of Usm On Tgf-β1/smad Pathwaymentioning
confidence: 99%
“…TGF-β is the major activator of collagen synthesis in human skin fibroblasts. The TGF-β type 1 receptor initiates the synthesis of type 1 procollagen [39]. UV irradiation impairs TGF-β and Smad2/3 signaling, decreasing type 1 procollagen synthesis, and leads to the loss of collagen in the dermis [11].…”
Section: Regulatory Effect Of Usm On Tgf-β1/smad Pathwaymentioning
confidence: 99%
“…It has been demonstrated in vitro and in vivo that daidzein promoted collagen deposition by stimulating collagen synthesis via up-regulating the expression of type I pro-collagen and inhibiting collagen degradation via down-regulating the levels of MMP1 (matrix metalloproteinase1), and MMP2. This collagen metabolic regulation was mediated by TGF-β/smad signal pathway, phosphorylated-smad2, smad3 and TGF-β was significantly higher in the daidzein-treated cells when compared to the control (Zhao et al, 2015). Exposure to solar UV radiation for a long time, in particular UVB radiation, accelerates skin aging due to induced production of oxygen free radicals in a study of pig skin model which is similar to the human skin.…”
Section: Anti-aging Activitymentioning
confidence: 83%